2023
DOI: 10.3389/fimmu.2023.1171826
|View full text |Cite
|
Sign up to set email alerts
|

The role of group 3 innate lymphoid cell in intestinal disease

Abstract: Group 3 innate lymphoid cells (ILC3s), a novel subpopulation of lymphocytes enriched in the intestinal mucosa, are currently considered as key sentinels in maintaining intestinal immune homeostasis. ILC3s can secrete a series of cytokines such as IL-22 to eliminate intestinal luminal antigens, promote epithelial tissue repair and mucosal barrier integrity, and regulate intestinal immunity by integrating multiple signals from the environment and the host. However, ILC3 dysfunction may be associated with the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…Therefore, SETD2 also indirectly contributes to intestinal homeostasis by influencing intestinal immunity. 44 …”
Section: Mainmentioning
confidence: 99%
“…Therefore, SETD2 also indirectly contributes to intestinal homeostasis by influencing intestinal immunity. 44 …”
Section: Mainmentioning
confidence: 99%
“…Indeed, it has been shown that murine norovirus (MNV) is capable of restoring architectural and immune status during gut bacterial dysbiosis [105]. The researchers hypothesized that the mechanism regulating host immune homeostasis in the GI tract was correlated with lymphocyte cell upregulation paired with IFNγ production and IgA release, allowing balance of type 2 and 3 innate lymphoid cell (ILC) ratios [106]. Interestingly, this also occurred during infection or inflammation, highlighting the possible protective role that some enteric viruses may play [107].…”
Section: Eukaryotic Viruses and The Gut Mucosal Immune Systemmentioning
confidence: 99%